1988
DOI: 10.2527/jas1988.6661438x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Dried Whey and Corn Oil on Weanling Pig Performance, Fat Digestibility and Nitrogen Utilization

Abstract: Two experiments were conducted to evaluate the effects and interactions of dietary levels of corn oil (0 vs 6%) and dried whey (0 vs 25%) on performance of young pigs during a 4-wk postweaning period. The first experiment, conducted in five replicates as a 2 x 2 factorial in a randomized block design, evaluated gain and feed intakes of 172 pigs weaned at 21 d of age. Pigs were bled at weekly intervals, and samples were assayed for serum triglyceride and urea concentrations. In a second experiment, 36 barrows i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
4

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 0 publications
5
16
0
4
Order By: Relevance
“…In many other reports, the addition of fat at the diet was known to improve feed efficiency during the post-weaning period (Cera et al, 1988; 1990; Howard et al, 1990; Li et al, 1990; Overland et al, 1993; Tokach et al, 1995). However, initial stage (from 0 to 14 d after weaning) was also no difference of feed efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…In many other reports, the addition of fat at the diet was known to improve feed efficiency during the post-weaning period (Cera et al, 1988; 1990; Howard et al, 1990; Li et al, 1990; Overland et al, 1993; Tokach et al, 1995). However, initial stage (from 0 to 14 d after weaning) was also no difference of feed efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have demonstrated that unsaturated lipids are more digestible than saturated lipids (Sewell and Miller, 1965;Carlson and Bayley, 1968;Hamilton and McDonald, 1969;Stahly, 1984;Cera et al, 1988b;Wiseman et al, 1990;Jørgensen et al, 1992;Øverland et al, 1994;NRC, 2012). We propose that this observation may be primarily related to the oxidative stability of SO.…”
Section: Methodsmentioning
confidence: 97%
“…A soja integral macerada continha 20,41% de extrato etéreo (EE) e sua inclusão nas dietas permitiu níveis de EE superiores aos encontrados na literatura para as atividades enzimáticas no trato digestivo dos leitões nas fases de vida estudadas (Lindemann et al, 1986;Cera et al, 1988).…”
Section: Methodsunclassified
“…A inclusão da soja integral macerada correspondeu, aproximadamente, a 7% de óleo nas dietas. Cera et al (1988) também constataram que o aumento da suplementação de óleo, até 6%, em dietas para leitões desmamados aos 21 dias de idade, reduziu a retenção do N dietético. Os autores sugeriram que os efeitos negativos ocorreram, principalmente, nas duas semanas subseqüentes ao desmame, pela redução da área de absorção, quando o comprimento das vilosidades do jejuno permaneceu curto.…”
Section: Variáveisunclassified